Family support system as a predictor of psychological well- being of the elderly in Ibadan metropolis, Oyo State (2020)
The study examined the family support System as a predictor of psychological well-being among the elderly in Ibadan Metropolis. Descriptive research design of the ex-post-facto type was used. A multi-stage sampling technique was used to select 180 aged respondents from 60 years and above from five local government areas in Ibadan Metropolis. Two research hypotheses were tested al 0.05 level of significance. Data were analyzed using t-test. Results indicated that aged people with low family support experienced higher anxiety level than their counterparts that received high family support. (t = 2.61, df = 178). Furthermore, aged people with low family support experienced higher depression level than their contemporaries with high family support (t =3.89, df = 178). It was recommended that government should provide free monthly medical check-up far the aged with particular focus on their mental and psychological health status